2013
DOI: 10.1371/journal.pone.0054894
|View full text |Cite
|
Sign up to set email alerts
|

‘The Words Will Pass with the Blowing Wind’: Staff and Parent Views of the Deferred Consent Process, with Prior Assent, Used in an Emergency Fluids Trial in Two African Hospitals

Abstract: ObjectiveTo document and explore the views and experiences of key stakeholders regarding the consent procedures of an emergency research clinical trial examining immediate fluid resuscitation strategies, and to discuss the implications for similar trials in future.MethodsA social science sub-study of the FEAST (Fluid Expansion As Supportive Therapy) trial. Interviews were held with trial team members (n = 30), health workers (n = 15) and parents (n = 51) from two purposively selected hospitals in Soroti, Ugand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 26 publications
5
67
2
Order By: Relevance
“…However, our results are consistent with other evidence indicating the acceptability of deferred consent to parents and to practitioners with experience of the process. 13,19,20 The higher consent rate for emergency compared with elective admissions may reflect a greater capacity for informed decision-making when parents were approached after the medical emergency had taken place, in a potentially less stressful environment. For elective admissions, parents may have felt responsible for…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results are consistent with other evidence indicating the acceptability of deferred consent to parents and to practitioners with experience of the process. 13,19,20 The higher consent rate for emergency compared with elective admissions may reflect a greater capacity for informed decision-making when parents were approached after the medical emergency had taken place, in a potentially less stressful environment. For elective admissions, parents may have felt responsible for…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence from parents indicates that being asked to make choices and to listen to information adds to the stressful environment of the pediatric setting. 20,21 This difference was reflected in the large proportion of parents of children admitted on an elective basis feeling too distressed and overwhelmed to engage with CATCH while having to focus on the impending surgical intervention. On the other hand, consent for emergency admissions was sought for use of data already collected and follow-up data collection only, because the intervention had already taken place.…”
Section: Figurementioning
confidence: 99%
“…38 However, it is questionable whether this approach is feasible and desirable because parents are still asked to consider information at a time when it is expected that they are unable to listen to, ask about, and understand the information. 39 Furthermore, even slight delays due to the prior permission-seeking process in emergency situations could lead to avoidable mortality and morbidity in trial participants and underestimate the beneficial effect of treatment. 40 When designing a study that will be implemented in an emergency setting, challenges with the consent process can reduce the number of recruited patients or lead to sampling bias, both of which may limit the study's value.…”
Section: Iii2 Potential Solutionsmentioning
confidence: 99%
“…Professionals without previous experience of deferred consent have been found to be apprehensive about the approach or find it inappropriate not to give parents any choice before starting the study. 35,39 On the other hand, approximately two-thirds of parents of critically ill children reported that deferred consent was acceptable to them, 41 or parents suggest that professionals should just get on with treating their child and worry about consent later. 39 These different viewpoints indicate the need for further discussion and reflection on the best practice regarding the informed consent process and to consult with parents (and, if feasible, young people) as partners in the design of consent procedures for trials that will be implemented in emergency settings.…”
Section: Iii2 Potential Solutionsmentioning
confidence: 99%
See 1 more Smart Citation